LEGAL DETERMINANTS FOR ANIMAL SLAUGHTERING, WITH THE PARTICULAR FOCUS ON RITUAL SLAUGHTER, UNDER THE POLISH AND ESTONIAN LEGISLATIONS - Spasowska-Czarny, Hanna (Review of European and Comparative Law, 2019)
The so-called ritual slaughter is one of the basic religious rules for adherents of Judaism and Islam. An important dimension of religious freedom is the freedom to perform acts of prayer and worship privately and publicly as well. Therefore, this also includes offering sacrifices and acquiring meat in accordance with tradition, which, in the case of adherents of Judaism and Islam, entails the practice of ritual slaughter. In European Union Member States, Council Regulation (EC) No 1099/2009 of 24 September 2009 on the protection of animals at killing has been effective since 1 January 2013. Under this regulation, animals are to be killed only after prior stunning, in accordance with the methods and detailed requirements related to the use of these methods as set out in Annex 1. The analysis of international law provisions indicates that although international law allows free practice of religious worship and related rites, the national legislature individually regulates the content of this legislation, taking into account the customary rules, principles and values ​​applicable in a given country, as well as the legislation aimed at protection of animals.